Analysis Of Drainage Channels In Bareng Village, Malang City Using SWMM (Storm Water Management Model) Application Simulation - Satriyo Arif Fauziansyah; Vita Ayu Kusuma Dewi (Universitas Islam Raden Rahmat, Malang, 2025)
Malang City is the second city in East Java, facing an increased risk of flooding due to population growth, changes in land use, and reduced infiltration areas. Jalan Bareng Raya II is one of the affected locations, with flooding occurring on April 29, 2023 due to high rainfall intensity. This study aims to evaluate the condition of the existing drainage network in the area using quantitative descriptive methods, including data collection, analysis, and interpretation of results. The SWMM (Storm Water Management Model) application is used to simulate overflow channels. Primary data was obtained from direct observation, while secondary data came from the Malang City PUPR Service and BPS. The SWMM simulations show 11 channels overflowing, which can be reduced with a combination of infiltration wells and biopores.